Research on copper-67 separation obtained by photo-nuclear from zinc of natural composition - Azarov, O.I.; Bocharov, V.O.; Stoyanov, O.F. (Вопросы атомной науки и техники, 2020)
In the world, it is planned to produce promising for the manufacture of radiopharmaceuticals of radioisotope copper-67 by the reaction of its production from zinc-68 under the influence of γ-radiation on an electron accelerator. The next major issue is the separation of copper and zinc. Extraction, ion exchange and thermal distillation of zinc have already been studied in detail. Co-precipitation of copper with low zinc and thermal distillation of organic compounds of metals is promising.